Cutaneous adverse reactions of COVID‐19 vaccines: A systematic review. Issue 5 (8th March 2022) - Qaderi, Kowsar; Golezar, Mohammad Hossein; Mardani, Abbas; Mallah, Manthar Ali; Moradi, Bagher; Kavoussi, Hossein; Shamsabadi, Ahmadreza; Golezar, Samira
Abstract: Numerous vaccines are under clinical development and implementation for the prevention of severe course and lethal outcomes of coronavirus disease 2019 (COVID‐19). This systematic review aims to summarize and integrated the findings of studies regarding cutaneous side effects of COVID‐19 vaccines. This systematic review conducted by searching the scientific databases of PubMed, Scopus, Science direct, and Web of knowledge from the beginning of the COVID‐19 to May 10, 2021. Articles were reviewed and analyzed based on the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses checklist. Seventeen studies on cutaneous side effects of COVID‐19 vaccines were included after the screening of search results based on to the eligibility criteria. The results showed that the most common injection site reactions and delayed large local reactions, arising from all vaccine types, were redness/erythema (39%), followed by: itchiness (28%), urticarial rash (17%) on the neck, upper limbs, and trunk, morbilliform eruptions (6.5%), Pityriasis rosea (3%), swelling, and burning, and so forth. Most cutaneous reactions occurred in women (84%), and middle‐aged people, after the first dose of vaccine, with the onset ranged from 1 to 21 days after vaccination. In addition, cutaneous reactions were generally self‐limiting, and needed little or no therapeutic intervention, that were not regarded as a barrier to injecting a second dose. In conclusion, severe cutaneous side effects are very rare and approved vaccines have satisfactory safety profiles. Therefore, mild or moderate cutaneous reactions should not discourage people from vaccination. In certain groups such as patients with allergies and a history of local injection reactions, pre‐vaccination counseling and assurance, also use of appropriate medications may be helpful. However, more studies are needed to investigate the side effect profile of all COVID‐19 vaccines.